The impact of the COVID-19 pandemic on the psychosocial well-being of undergraduate students in south India- a cross sectional study - Christy Jacob, Leo; Johnson, Jeff; John, Mariah; Maria Regy, Minitta; Shanbhag, Deepthi (International Journal of Research in Medical Sciences, 2023)
Background: There is an increasing concern on the psychosocial well-being of students especially being vulnerable during times such as the pandemic. Objective were (i) to assess the prevalence of psychosocial issues and coping skills over the lockdown period due to the covid pandemic among undergraduate students in India, (ii) to associate the various factors affecting the study pattern over the lockdown period among the same population. Methods: This was an online cross-sectional study among undergraduate students studying in various south-Indian colleges done during the initial lockdown (May to September 2020). We followed snowball sampling and collected data using google forms with study tools such as, standard revised UCLA loneliness scale and WHO 5 well-being index questionnaire. Our final data of 350 (from 378) was then analyzed using IBM SPSS v21.0 and based on Likert scaling, we graded our responses to assess the severity of loneliness and well-being. Results: The mean age was 23.1±3.31 years and majority of participants belonged to the age group of 21-23 (58.3%). Majority of the participants were pursuing a medical course (62%) and were in their second year of professional course (39.7%). According to WHO-5 scale, 115 (32.9%) had poor well-being and 235 (67.1%) had good well-being and further on comparing it was observed that those with severe loneliness (N=16.7%) had 0.010 times lesser chance of having good well-being (p=0.000) than those who had no loneliness (N=95%). Conclusions: Vulnerable and changing times such as these contribute for alteration in a growing adult’s progress towards well-being.